2017
DOI: 10.1016/j.cemconcomp.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The durability of cementitious composites containing microencapsulated phase change materials

Abstract: This study investigates the durability of cementitious composites containing microencapsulated phase change materials (PCMs). First, the stability of the PCM's enthalpy of phase change was examined. A reductionof around25% in the phase change enthalpy was observed, irrespective of PCM dosage and aging. Significantly, this reduction in enthalpy was not caused by mechanical damage that was induced during mixing, but rather by chemical interactions with dissolved SO 4 2ions. Second, the influence of PCM additions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 42 publications
(53 reference statements)
3
42
0
Order By: Relevance
“…Figure 1: (a) A scanning electron micrograph of "core-shell" microencapsulated phase change materials (PCMs) wherein the core is the active phase change component (e.g., often alkanes of composition CnH2n+2) and the shell is a polymer structure often comprised of melamineformaldehyde (MF) (N.B. : Only the MF shell is visible in this image ‡ ‡ ) [9], and, (b) The compressive strength, fc, of cementitious mixtures containing quartz or microencapsulated PCM inclusions after 28 days of aging as a function of the inclusion volume fraction (VF) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1: (a) A scanning electron micrograph of "core-shell" microencapsulated phase change materials (PCMs) wherein the core is the active phase change component (e.g., often alkanes of composition CnH2n+2) and the shell is a polymer structure often comprised of melamineformaldehyde (MF) (N.B. : Only the MF shell is visible in this image ‡ ‡ ) [9], and, (b) The compressive strength, fc, of cementitious mixtures containing quartz or microencapsulated PCM inclusions after 28 days of aging as a function of the inclusion volume fraction (VF) [10].…”
Section: Introductionmentioning
confidence: 99%
“…For application in buildings, the coating needs to achieve a good compromise between hardened state properties and heat transfer, so 20% PCM will be more beneficial for the mortar's durability. It has been demonstrated that the presence of PCM capsules in mortars [46], even with several cooling and melting cycles, does not affect its durability-it was not observed any cracking in the mortars' layers of the cells subject to thermal cycling.…”
Section: Resultsmentioning
confidence: 99%
“…Wei et al reported the durability of cementitious composite containing commercially available micro‐PCMs. The results revealed that micro‐PCMs reduced the rate and extent of water sorption and did not affect the dry shrinkage of cementitious composites.…”
Section: Application Of Micro‐/nano‐pcmsmentioning
confidence: 99%